Effects of aerobic exercise on integrated cardiovascular health and energy metabolism in patients with type 2 diabetes mellitus: study protocol for a randomized controlled trial - Wang, Shihe; Liu, Zhouyu; Feng, Ning; Guo, Yaodong; Chen, Qi; Cao, Yiyang; Li, Xuelu; Liu, Xiao; Yan, Zhiwei (Frontiers in Endocrinology, 2026)
ObjectiveType 2 diabetes mellitus (T2DM) induces integrated cardiovascular and metabolic impairments. The comprehensive effect of aerobic exercise on these systemic alterations remains unclear. Therefore, we designed a randomized controlled trial to investigate its impact on integrated cardiovascular health — specifically assessed by nitroglycerin-mediated dilation (NMD) and myocardial global work efficiency (GWE) — and systemic energy metabolism in patients with T2DM.MethodsThis study is a randomized, single-assessor-blind, parallel-group, two-arm controlled trial that will enroll 74 patients with T2DM. Participants will be randomly assigned in a 1:1 ratio to either a 12-week supervised aerobic exercise group (55–75% of HRpeak, three times per week) or a non-exercise control group. The primary outcomes are the changes from baseline to 12 weeks in NMD and GWE. Secondary outcomes include key cardiometabolic indicators (energy metabolism, insulin levels), office and 24-hour ambulatory blood pressure, cardiovascular risk factors, 24-hour movement behavior, cardiopulmonary function, arterial stiffness (baPWV), vascular endothelial function (FMD), cardiac electrical activity, echocardiographic parameters, and self-reported fatigue. Additional exploratory variables include markers of myocardial injury and skeletal muscle injury, circulating markers of oxidative stress and inflammation, central fatigue biomarkers, and levels of cardiovascular-related hormones. Recruitment began in June 2025 and is currently ongoing.DiscussionThis study provides an integrated physiological perspective on how 12-week moderate-intensity aerobic exercise influences cardiovascular function and systemic metabolism in patients with T2DM. We hypothesize that 12 weeks of aerobic exercise will significantly improve NMD and GWE, concurrent with enhanced metabolic flexibility and reduced fatigue compared to the non-exercise control group.